Embodied digital warfare: authoritarian appropriation through human enhancement - Ruppert, LInda; Bork-Hüffer, Tabea (Dialogues on digital society, 2025)
While current debates on digital warfare are often centered on autonomous weapons or cyberwarfare, a growing “arms race” targeting the human body through human augmentation (HA) and human enhancement (HE) technologies is often neglected. Taking the example of a recent German-UK joint defence strategy paper, this commentary explores how HA and HE—such as brain-computer interfaces and augmented reality technologies—reengineer the vulnerable soldier's body for warfare, often intertwined with authoritarian war politics. While framed as keeping “the human in the loop,” HA and HE expose tensions between human limits, technological demands, and singular notions of body-technology relations. We conceptualize HA and HE as embodied digital warfare: a mode of authoritarian appropriation, reengineering, and representation of soldiers’ bodies through technology in service of war politics.
First published online: August 21, 2025
Gesehen am 22.08.2025